Interactive Control System Analysis On Corporate Sustainability Performance : Good Corporate Governance as Mediating Variable - Triwacananingrum, Wijaya (AKRUAL: Jurnal Akuntansi, 2018)
The purpose of this research is to test how the measurement of interactive control system can improve corporate sustainability performance through good corporate governance. This research is a survey study with the object of research of decision makers of echelon 2 and up level in Semen Indonesia, by distributing questionnaires. In analyzing the data used structural equation modeling. Measurement model to test reliability and validity while the model structural measurement is measured by the mean R2 for the dependent variable and the path coefficient test. Out of 39 questionnaires collected, 33 questionnaires were eligible for processing. The results showed a positive relationship between Interactive Control on Corporate Governance, negative relationship between Corporate Governance to Sustainability Corporate Performance, and positive relationship between Interactive Control to Sustainability Corporate Performance. So the interactive control system can directly improve corporate sustainability performance, while good corporate governance. Can not mediate the relationship of interactive control system and corporate sustainability performance.